BE_ZIVILSTRAF ZK 2011 145 vom 14. Juli 2011 - BE Obergericht (2011)
Überführung einer Einzelunternehmung in eine neu zu gründende Aktiengesellschaft | Handelsregister/Geschäftsfirmen/kaufmännische Buchführung